أثر مفهوم المنهج التربوي تقليديا وحديثا في منهج اللغة العربية - M. Fathor Rohman (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The development of the curriculum concept from traditional to modern has led to comprehensive developments in the components and factors that influence the educational curriculum. This is a positive progress of the curriculum concept because what characterizes an ideal curriculum is that it is variable and flexible to follow developments in the environment and time. The method used in this research uses a library research method or approach. Data collection in this research was carried out by reviewing and/or exploring several journals, books and documents (both printed and electronic) as well as data sources. and/or other information deemed relevant to the research or study. The results of this research are that the curriculum in the modern sense is more positive than the curriculum in the traditional sense in developing students or students and developing them comprehensively. This is also more positive in developing the quality of the education and learning process. Therefore, those in charge of Arabic language subjects need to understand the curriculum in a modern sense so that students do not fall into dilemmas and are left behind due to staff or school officials adhering to traditional curriculum concepts.